2012
DOI: 10.1111/j.1526-4610.2012.02210.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Disorders in Children and Adolescents: Their Association With Psychological, Behavioral, and Socio‐Environmental Factors

Abstract: A common path model as posited by several researchers in the field may explain the parallelism in biopsychosocial vulnerability regarding the different headache disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 68 publications
(132 reference statements)
4
44
1
2
Order By: Relevance
“…Kroner-Herwig and Gassmann found that primary headaches were significantly higher among females. 23 This is similar to this analysis in which significantly more female students reported suffering from headaches than male students.…”
Section: Demographic Characteristicssupporting
confidence: 78%
“…Kroner-Herwig and Gassmann found that primary headaches were significantly higher among females. 23 This is similar to this analysis in which significantly more female students reported suffering from headaches than male students.…”
Section: Demographic Characteristicssupporting
confidence: 78%
“…Previous studies on adolescents also found associations between the prevalence of TMD and sex, 9,12,43 and an association between pubertal development and TMD pain both in boys and in girls has been observed. 43 Girls seem to be more likely to report HAs compared with boys 15,23,29,43,44 and it is speculated that a combination of developmental and hormonal changes would be responsible for increasing HAs in girls after menarche. 45 However, this hypothesis was not confirmed in the present study because statistical differences were not found when comparing girls before and after menarche either for the presence of painful TMD or for HAs.…”
Section: Discussionmentioning
confidence: 96%
“…If this is the case, then biopsychosocial factors that may underlie these differences in prevalence should be further explored for TMD as they were for HA. 23 HAs are one of the most common symptoms reported by TMD patients, 31 justifying the high degree of association between HAs and painful TMD. Two hypotheses could explain the significant association between TMD and HAs in the sample of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The irritable bowel syndrome (IBS) clinical manifestations, disease behaviors and future outcomes are also under the impact of this dysfunction. also adopted in many pain related disorders such as migraine, tension headache, chronic fatigue syndrome, and fibromyalgia [28,29] . Thereafter, a concept of central sensitivity syndromes is proposed to unite these comorbidities that apparently share the same biopsychosocial dysfunction [30,31] .…”
Section: Biopsychosocial Modelmentioning
confidence: 99%